Trajectory of hearing loss in children with unilateral hearing loss - Fitzpatrick, Elizabeth M.; Nassrallah, Flora; Gaboury, Isabelle; Whittingham, JoAnne; Vos, Bénédicte; Coyle, Doug; Durieux-Smith, Andrée; Pigeon, Marie; Olds, Janet (Frontiers in Pediatrics, 2023)
Introduction. The aim of this study was to quantify the amount of deterioration in hearing and to document the trajectory of hearing loss in early identified children with unilateral hearing loss (UHL). We also examined whether clinical characteristics were associated with the likelihood of having progressive hearing loss. Methods. As part of the Mild and Unilateral Hearing Loss Study, we followed a population-based cohort of 177 children diagnosed with UHL from 2003-2018. We applied linear mixed models to examine hearing trends over time including the average amount of change in hearing. Logistic regression models were used to examine the relationship between age and severity at diagnosis, etiology, and the likelihood of progressive loss and amount of deterioration in hearing. Results. The median age of the children at diagnosis was 4.1 months (IQR 2.1, 53.9) and follow-up time was 58.9 months (35.6, 92.0). Average hearing loss in the impaired ear was 58.8 dB HL (SD 28.5). Over the 16-year period, 47.5% (84/177) of children showed deterioration in hearing in one or both ears from initial diagnosis to most recent assessment including 21 (11.9%) who developed bilateral hearing loss. Average deterioration in the impaired ear ranged from 27 to 31 dB with little variation across frequencies. Deterioration resulted in a change in category of severity for 67.5% (52/77) of the children. Analysis for children who were followed for at least eight years showed that most lost a significant amount of hearing rapidly in the first 4 years, with the decrease stabilizing and showing a plateau in the last 4 years. Age and severity at diagnosis were not significantly associated with progressive/stable loss after adjusting for time since diagnosis. Etiologic factors (hereditary/genetic, ENT anomalies, external/middle ear anomalies, syndromic hearing loss) were found to be positively associated with stable hearing loss. Conclusions. Almost half of children with UHL are at risk for deterioration in hearing in one or both ears. Most deterioration occurs within the first four years following diagnosis. These results suggest that careful monitoring of UHL especially in the early years is important to ensure optimal benefit from early hearing loss detection.